Uncertainty Analysis on k-ε Turbulence Model in the Prediction of Subcooled Boiling in Vertical Pipes - Zhang, Xiang; Xia, Genglei; Cong, Tenglong; Peng, Minjun; Wang, Zhenhong (Frontiers in Energy Research, 2020)
Computational fluid dynamics (CFD) has become an effective method to research the two-phase flow in reactor systems. However, it is still immature that the uncertainty analysis of CFD simulation is. The effects of uncertainties from the two-phase models and boundary conditions have been analyzed in our previous work. In this work, the uncertainties from turbulence model on the prediction of subcooled boiling flow were analyzed with the DEBORA benchmark experiments by deterministic sampling method. Seven parameters in standard k-ε model interrelated momentum, energy, turbulent kinetic energy and dissipation rate were studied as uncertainty sources, including Cμ, Cμ,g, C1ε, C2ε, σk, σε and Prt. Radial parameters were calculated to study the effects of uncertainties from turbulence model. The contributions of each uncertainty source to void fraction and liquid temperature were also analyzed. It is found that the models can simulate subcooled boiling well and the uncertainty analysis by deterministic sampling can give a reference interval to increase the reliability of results. The C2ε and C1ε, parameters in production term and dissipation term of transport equations, dominate the radial distributions of void fraction and liquid temperature.